New records of the archaic dolphin Agorophius (Mammalia: Cetacea) from the upper Oligocene Chandler Bridge Formation of South Carolina, USA - Robert W. Boessenecker; Jonathan H. Geisler (PeerJ, 2018)
The stem odontocete Agorophius pygmaeus (Ashley Formation, lower Oligocene, South Carolina; 29.0–26.57 Ma) has been a critical point of comparison for studies of early neocete evolution owing to its early discovery as well as its transitional anatomy relative to archaeocete whales and modern odontocetes. Some time during the late nineteenth century the holotype skull went missing and has never been relocated; supplementary reference specimens have since been recently referred to the species from the Ashley Formation and the overlying Chandler Bridge Formation (upper Oligocene; 24.7–23.5). New crania referable to Agorophius sp. are identifiable to the genus based on several features of the intertemporal region. Furthermore, all published specimens from the Chandler Bridge Formation consistently share larger absolute size and a proportionally shorter exposure of the parietal in the skull roof than specimens from the Ashley Formation (including the holotype). Furthermore, these specimens include well-preserved ethmoid labyrinths and cribriform plates, indicating that Agorophius primitively retained a strong olfactory sense. These new crania suggest that at least two species of Agorophius are present in the Oligocene of South Carolina, revealing a somewhat more complicated taxonomic perspective.